2021
DOI: 10.3390/en14061581
|View full text |Cite
|
Sign up to set email alerts
|

Load Frequency Control Using Hybrid Intelligent Optimization Technique for Multi-Source Power Systems

Abstract: The automatic load frequency control for multi-area power systems has been a challenging task for power system engineers. The complexity of this task further increases with the incorporation of multiple sources of power generation. For multi-source power system, this paper presents a new heuristic-based hybrid optimization technique to achieve the objective of automatic load frequency control. In particular, the proposed optimization technique regulates the frequency deviation and the tie-line power in multi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…The summarized frequency responses of the simulation tests conducted in this research were discussed and compared to the related recent research outputs as described in [14][15][16][17], and [18]. The observed results showed the sensitivity of the developed control system by 99.86% 3 illustrates the smallest frequency characteristics of 0.000015 Hz, 0.0000012 Hz, and 0.251 s; 0.13 Hz, 0 Hz, and 0.251 s for overshoot, frequency steady-state error, and settling time were successfully observed and saved the 75 Megawatts loss respectively by weighing with the related research findings.…”
Section: Case Study 1: Single Area Power Generationmentioning
confidence: 99%
“…The summarized frequency responses of the simulation tests conducted in this research were discussed and compared to the related recent research outputs as described in [14][15][16][17], and [18]. The observed results showed the sensitivity of the developed control system by 99.86% 3 illustrates the smallest frequency characteristics of 0.000015 Hz, 0.0000012 Hz, and 0.251 s; 0.13 Hz, 0 Hz, and 0.251 s for overshoot, frequency steady-state error, and settling time were successfully observed and saved the 75 Megawatts loss respectively by weighing with the related research findings.…”
Section: Case Study 1: Single Area Power Generationmentioning
confidence: 99%
“…where K pr , and K i , are the controller parameters. In this paper, we consider the objective function as an integral time absolute error (ITAE) [23]. The ITAE cost function is as given by Equation ( 2) below.…”
Section: The Proportional Plus Integral Controllermentioning
confidence: 99%
“…A comparative analysis of several soft computing techniques for the LFC have been studied in [21] by Gupta et al Further, for a power system with interconnected areas, load frequency control analysis has been carried out in [22] using a hybrid adaptive gravitational search and pattern search algorithm. Recently, Gupta et al reported novel hybrid optimization techniques for addressing the issues of LFC in MAPS comprising multiple sources [23]. Koley et al [24] presented the issue of LFC by considering a power system involving hybrid power plants such as thermal, wind, and photovoltaic generation stations.…”
Section: Introductionmentioning
confidence: 99%
“…The essential features of LFC are (i) to abolish the frequency error, (ii) to retain the steady power flow over transmission lines, and (iii) to uphold synchronization between the associated generators. The foremost concern of today's power system is to deliver eminence power against incessant load fluctuation, swift mounting load demand, interconnected large power networks, and dispersion of renewable energy sources [1][2]. From time to time, the foremost power production by thermal and hydro sources is not appropriate for  ISSN: 2089-3272 IJEEI, Vol.…”
Section: Introductionmentioning
confidence: 99%